2006
DOI: 10.1002/adfm.200500561
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Adsorption in Metal–Organic Frameworks: Cu‐MOFs and Zn‐MOFs Compared

Abstract: Hydrogen adsorption in two different metal–organic frameworks (MOFs), MOF‐5 and Cu‐BTC (BTC: benzene‐1,3,5‐tricarboxylate), with Zn2+ and Cu2+ as central metal ions, respectively, is investigated at temperatures ranging from 77 K to room temperature. The process responsible for hydrogen storage in these MOFs is pure physical adsorption with a heat of adsorption of approximately –4 kJ mol–1. With a saturation value of 5.1 wt.‐% for the hydrogen uptake at high pressures and 77 K, MOF‐5 shows the highest storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
370
3
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(434 citation statements)
references
References 25 publications
(38 reference statements)
40
370
3
12
Order By: Relevance
“…Figure 4a shows the simulated adsorption isotherm of the H2 adsorption in MOF-5 at 298 K compared with the experimental data [29]. The simulated adsorption isotherm fits well with the experimental data at different pressures, with the standard deviation being less than 6.57%.…”
Section: Simulation Methodssupporting
confidence: 50%
“…Figure 4a shows the simulated adsorption isotherm of the H2 adsorption in MOF-5 at 298 K compared with the experimental data [29]. The simulated adsorption isotherm fits well with the experimental data at different pressures, with the standard deviation being less than 6.57%.…”
Section: Simulation Methodssupporting
confidence: 50%
“…Cu-MOF has a greater capacity to adsorb higher hydrogen than does Zn-MOF (Panella et al, 2006). When Cu-MOF was used as the catalyst for "Click" reactions, it was found that different organic linkers in the MOF influenced catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Through the careful choice of starting materials, these networks can be tailored for specific magnetic or catalytic properties, as well as for other applications such as gas storage. 19,44 The creation of MOCNs directly at surfaces is considered to be relevant for similar technological applications including information storage and processing 5,40,45 and also constitutes a model system to study low-dimensional magnetism at surfaces. 34,35 A typical linker molecule used for surface MOCNs is trimesic acid (TMA) comprised of three carboxylic acid groups ordered in a planar triangular arrangement around the central phenyl ring, Figure 1.…”
Section: Introductionmentioning
confidence: 99%